EXTORTION OF TESTIMONY IN CRIMINAL PROCEEDINGS THROUGH THE PRISM OF THE WORK OF THE POLICE AND THE PROSECUTOR’S OFFICE - Садмир Каровић; Марина М. Симовић (Годишњак Правног факултета у Бањалуци)
In this paper, attention is focused on the criminal offense of extortion of statement, with the intention of the author to take a comprehensive look at the criminal law (substantive) and procedural aspect of this criminal offense. The application of repression in itself always represents a challenge in terms of legal application by persons entrusted with certain powers, given the tendency to humanize modern criminal law in Bosnia and Herzegovina, which sets high standards for competent procedural subjects. In connection with the above, the component of the efficiency of the investigation and the criminal procedure in general must not in any case be at the expense of respecting the basic human rights and freedoms of the participants in the criminal procedure. The actions of competent procedural entities are prescribed and conditioned by restrictive legal conditions in all procedural stages, starting from the initial knowledge (grounds of suspicion) of the existence of a criminal case until the end of the criminal proceedings. Precisely because of the above, it is necessary to observe this criminal offense through the prism of the general legal and social context, in order to understand properly the legal nature as well as the material and procedural specifics of the criminal offense of extortion of testimony.